2015
DOI: 10.4028/www.scientific.net/jnanor.35.67
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography, Impurities and Magnetic Properties of Mn-Doped ZnO Nanoparticles Prepared by Coprecipitation Method

Abstract: Introduction of Mn2+ions into ZnO in the form of Zn(1-x)MnxO (0.00≤x≤0.25) has been done by means of coprecipitation method at low temperature using Zn(CH3COO)2·2H2O, Mn(CH3COO)2·4H2O, HCl, and NH4OH as starting materials. The XRD analysis showed that the produced Zn(1-x)MnxO (0.00≤x≤0.09) samples were crystallized in single phase of wurtzite with hexagonal structures. Besides the wurtzite, the presence of the secondary phase of hetaerolite ZnMn2O4with tetragonal structures was detected in the samples having 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…Meanwhile, the increase of Mn content may lead to Mn clusters in the ZnO matrix. Many authors (Harsono et al, 2017;Luo et al, 2014;Subramanian et al, 2011;Hao et al, 2012) have also reported the same trend for our samples.…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, the increase of Mn content may lead to Mn clusters in the ZnO matrix. Many authors (Harsono et al, 2017;Luo et al, 2014;Subramanian et al, 2011;Hao et al, 2012) have also reported the same trend for our samples.…”
Section: Figuresupporting
confidence: 87%
“…As mentioned above, due to the unique optoelectronic performance of ZnO nanostructures, they have wide application in LEDs, lasers, solar cells and optical/ radiation sensors (O ¨zgu ¨r et al, 2005;Schmidt-Mende & MacManus-Driscoll, 2007). Many researchers in nanotechnology have used a variety of methods to synthesize zinc oxide NPs doped with mono-doping or co-doping transition metal ions (Mn, Fe, Co, Ni, Cr); for example, sol-gel (Khorsand Zak et al, 2012;Liu et al, 2010), spray (Shinde et al, 2006), radio-frequency magnetron sputtering (Ashida et al, 2006), pulsed laser deposition (Tiwari et al, 2002), metal organic deposition (Tuan et al, 2004) and co-precipitation (Harsono et al, 2017;Tan et al, 2014;Bagheri et al, 2013). Also, -ray irradiation has been used for the preparation of metal oxides (Imam et al, 2021a).…”
mentioning
confidence: 99%
“…The series of Zn(1-x)MnxO (MZO) nanoparticles were prepared by the coprecipitation method as reported in [16]. Here, we focus on MZO with x= 0.03 (MZO3), 0.05 (MZO5) and 0.07 (MZO7) as a crossover of paramagnetic to superparamagnetic-like state has been suggested to occurs at this concentration range [16].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, one can expect the increase in the magnetic moment of MZO by increasing the concentration of either Mn or charge carriers via the introduction of oxygen vacancy. The magnetism of MZO has been intensively studied [9,[11][12][13][14][15][16][17]. It was reported that MZO thin films have ferromagnetic feature at room temperature [12,13], while polycrystalline MZO exhibits paramagnetic behavior even at 15% of Mn-concentration [11,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation